2006
DOI: 10.1002/ajh.20653
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS13 activity in sickle cell disease

Abstract: Sickle red blood cell (SRBC)-endothelial adhesion plays a central role in sickle cell disease (SCD)-related vaso-occlusion. As unusually large von Willebrand factor (ULVWF) multimers mediate SRBC-endothelial adhesion, we investigated the activity of ADAMTS13, the metalloprotease responsible for cleaving ULVWF multimers, in SCD. ADAMTS13 activity was determined using a quantitative immunoblotting assay. VWF:Ag and VWF:RCo were determined using commercial assays. The high-molecular-weight VWF multimer percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 41 publications
8
46
0
2
Order By: Relevance
“…This process may ultimately result in organ dysfunction as described previously in several other pathologies and invasive procedures including TTP and liver transplantation (4,5,(20)(21)(22)(23)(24). We speculate that the development of a VWF/ADAMTS13 unbalance during lung transplantation also facilitates thrombus formation within the allograft.…”
Section: Primary Hemostasis In Lung Transplantationsupporting
confidence: 59%
“…This process may ultimately result in organ dysfunction as described previously in several other pathologies and invasive procedures including TTP and liver transplantation (4,5,(20)(21)(22)(23)(24). We speculate that the development of a VWF/ADAMTS13 unbalance during lung transplantation also facilitates thrombus formation within the allograft.…”
Section: Primary Hemostasis In Lung Transplantationsupporting
confidence: 59%
“…A doubleblind randomized trial with tinzaparin in SCD patients during acute vaso-occlusive events documented a reduction of their severity and duration [97]. Studies with low dose of warfarin or acenocoumarol were reported to slightly reduce the frequency of acute pain events with decreased thrombin generation and fibrinolysis, however without reaching a significant clinical amelioration [98].…”
Section: Future Trendmentioning
confidence: 99%
“…[8][9][10] Normally, ULVWF is cleaved rapidly by the metalloproteinase ADAMTS13 into smaller, less adhesive multimers, 11 preventing disastrous complications, such as thrombotic thrombocytopenic purpura. 12 Elevated plasma VWF levels have been reported in SCD, 13,14 but studies on the structure and reactivity of VWF in this disease are lacking.…”
Section: Introductionmentioning
confidence: 99%